2019
DOI: 10.3390/ma12203410
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Different Superplasticizers and Retarders on Properties of ‘One-Part’ Fly Ash-Slag Blended Geopolymers with Different Activators

Abstract: Currently, there are a very limited number of studies on the effect of admixtures on properties of ‘one-part’ geopolymers. This paper reports the effects of different superplasticizers and retarders on fresh and hardened properties of one-part fly ash-slag blended geopolymers made by different solid activators. Two different grades of sodium silicate, namely anhydrous sodium metasilicate powder (nSiO2/nNa2O = 0.9) and GD Grade sodium silicate powder (nSiO2/nNa2O = 2.0) were used as the solid activators. Five d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 62 publications
1
20
0
Order By: Relevance
“…The superplasticizer density was 1.1 kg/L. The chloride content was less than 0.1%, and the alkaline content was less than 3%, which confirms Bong et al [ 52 ].…”
Section: Methodssupporting
confidence: 80%
“…The superplasticizer density was 1.1 kg/L. The chloride content was less than 0.1%, and the alkaline content was less than 3%, which confirms Bong et al [ 52 ].…”
Section: Methodssupporting
confidence: 80%
“…According to the authors [ 20 ], 6 wt.% of borax is the suitable amount since it improved the paste fluidity without significantly affect the mechanical properties of the samples. Bong et al [ 21 ], besides testing the effect of additives, studied two activators (as powder): Anhydrous sodium metasilicate and sodium silicate. The authors observed that the workability and setting time of the AMMs mixtures prepared with sodium silicate did not fill the requirements, even when additives were used, and a decrease of the compressive strength was observed.…”
Section: Introductionmentioning
confidence: 99%
“…A study regarding the effects of sucrose on the hydration of C 3 S (i.e., a main hydrous phase in ordinary portland cement) confirmed the adsorption of sucrose at hydrated silicate sites based on NMR characterizations, 35 further suggesting the potential of sucrose to control the reaction kinetic of aluminosilicates. However, to the best of our knowledge, as also discussed above, the effects of sucrose on setting have been investigated only in geopolymer pastes that contain additional calcium or portland cement 22,36‐38 …”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, as also discussed above, the effects of sucrose on setting have been investigated only in geopolymer pastes that contain additional calcium or portland cement. 22,[36][37][38] Our objective in this study is to examine the effects of sucrose on the reaction kinetics of non-calcium geopolymers, including both metakaolin-based samples and synthetic gels. Metakaolin is a pure and amorphous aluminosilicate precursor material that facilitates any mechanistic understanding of the reaction kinetics of geopolymers.…”
mentioning
confidence: 99%